Ultraviolet B Radiation Enhances a Phytochrome-B-Mediated Photomorphogenic Response in Arabidopsis - Boccalandro, Hernán E. (American Society of Plant Physiologists, 2001)
Ultraviolet B radiation (UV-B, 290–315 nm) can cause damage and induce photomorphogenic responses in plants. The mechanisms that mediate the photomorphogenic effects of UV-B are unclear. In etiolated Arabidopsis seedlings, a daily exposure to 2.5 h of UV-B enhanced the cotyledon opening response induced by a subsequent red light (R) pulse. An R pulse alone, 2.5 h of UV-B terminated with a far-red pulse, or 2.5 h of continuous R caused very little cotyledon opening. The enhancing effect of UV-B increased with fluence rate up to approximately 7.58 μmol m(−2) s(−1); at higher fluence rates the response to UV-B was greatly reduced. The phyA, phyA cry1, and cry1 cry2 mutants behaved like the wild type when exposed to UV-B followed by an R pulse. In contrast, phyB, phyB cry1, and phyB phyA mutants failed to open the cotyledons. Thus, phytochrome B was required for the cotyledon opening response to UV-B → R treatments, whereas phytochrome A and cryptochromes 1 and 2 were not necessary under the conditions of our experiments. The enhancing effect of low doses of UV-B on cotyledon opening in uvr1 uvr2 and uvr1 uvr3 mutants, deficient in DNA repair, was similar to that found in the wild type, suggesting that this effect of UV-B was not elicited by signals derived from UV-B-induced DNA lesions (cyclobutane pyrimidine dimers and 6-4 photoproducts). We conclude that low doses of UV-B, perceived by a receptor system different from phytochromes, cryptochromes, or DNA, enhance a de-etiolation response that is induced by active phytochrome B.